Factors that Influence the Productivity of Green Bean Farming in Demak District - Muflihah, Ufi (Universitas Negeri Semarang, 2019)
Demak regency is the center of green bean however, the productivity of green beans in Demak Regency has decreased during 2009-2016. The aims of study is determine the effect of land area, seeds, labor, fertilizer, pesticides on the productivity of green beans. This type of research is quantitative research. The data used was primary data. The population in this study is that farmers in Demak Regency with samples of mung bean farmers in Demak Regency totaled 100 people. The analytical method uses descriptive analysis and multiple linear regression analysis with the Ordinary Least Square (OLS) method through the Cobb-Douglas production function model. From the results of this study showed that area of land, fertilizer, pecticides have a significant positive effect on the productivity of green beans which every increase in labor will reduce productivity of green beans, while the seeds have no significant positive effect on the productivity of green beans which increase in the number of seeds does not affect the productivity of green beans. The suggestion of this reserach are that the unused area further improved itd use, the seeds are planted with better planting methods that will is not easily damaged by the weather, there should be a division of labor in green bean farming so that the workers can work productively, the intensity of spraying fertilizers can be improved to increase green bean production, the intensity of spraying of pesticides can be increased to minimize the harvest of crops. Kabupaten Demak adalah pusat kacang hijau, namun produktivitas kacang hijau di Kabupaten Demak mengalami penurunan selama 2009-2016. Tujuan penelitian adalah mengetahui pengaruh luas lahan, benih, tenaga kerja, pupuk, pestisida terhadap produktivitas kacang hijau. Jenis penelitian ini adalah penelitian kuantitatif. Data yang digunakan adalah data primer. Populasi dalam penelitian ini adalah petani di Kabupaten Demak dengan sampel petani kacang hijau di Kabupaten Demak berjumlah 100 orang. Metode analisis menggunakan analisis deskriptif dan analisis regresi linier berganda dengan metode Ordinary Least Square (OLS) melalui model fungsi produksi Cobb-Douglas. Dari hasil penelitian ini menunjukkan bahwa luas lahan, pupuk, pektisida berpengaruh positif signifikan terhadap produktivitas kacang hijau dimana setiap peningkatan tenaga kerja akan menurunkan produktivitas kacang hijau, sedangkan benih tidak berpengaruh positif signifikan terhadap produktivitas tanaman hijau. kacang hijau yang meningkatkan jumlah biji tidak mempengaruhi produktivitas kacang hijau. Saran dari penelitian ini adalah agar daerah yang tidak digunakan semakin ditingkatkan penggunaannya, benih ditanam dengan metode penanaman yang lebih baik sehingga tidak mudah rusak oleh cuaca, harus ada pembagian kerja dalam pertanian kacang hijau sehingga para pekerja dapat bekerja Secara produktif, intensitas penyemprotan pupuk dapat ditingkatkan untuk meningkatkan produksi kacang hijau, intensitas penyemprotan pestisida dapat ditingkatkan untuk meminimalkan panen tanaman